Clinical management of casualties exposed to lung damaging agents: a critical review. Issue 6 (19th May 2006) - Russell, D; Blain, P G; Rice, P
Abstract : There is no specific antidote for the treatment of casualties exposed to chlorine, phosgene, or mustards; therefore, management is largely supportive. Corticosteroid treatment has been given to casualties accidentally exposed to chlorine. Clinical data on efficacy are inconclusive as the numbers given steroids have been small and the indications for administration unclear. There have been no clinical controlled studies. There is a stronger evidence base from animal studies, particularly from porcine and rodent models. Lung injury induced by phosgene and mustard appears to be mediated by glutathione depletion, lipid peroxidation, free radical generation, and subsequent cellular toxicity. There is limited evidence to suggest that repletion of glutathione reduces and/or prevents lung damage by these agents. This may provide an opportunity for therapeutic intervention.